Strategi PIC (Person In Charge) Dalam Membangun Komunikasi Eksternal Terkait Penanganan Masalah Registrasi Data Terpadu Kesejahteraan Sosial: Studi Kasus di Dinas Sosial Kota Tangerang Selatan - Maysyarah, Maya; Seran, Adrianus; Santoso, Ade Budi (Prisani Cendekia Institute, 2023)
Communication strategy is very important for a communicator in developing communication with other parties. This research is motivated by the phenomenon of registration problems DTKS (Integrated Social Welfare Data) in the South Tangerang area so that good communication is needed between the Social Service and the community as an external public. This research examines the PIC (person in charge) strategy in building communication with the community as an external public at the South Tangerang City Social Service regarding the problem of DTKS registration for the poor. The purpose of this study was to find out the communication strategy carried out by PIC, the communication process, the obstacles faced in establishing communication and registration problems as well as the causes of the soaring number of DTKS in the South Tangerang area. This research was conducted using descriptive qualitative research methods by conducting observations, interviews and documentation of documents and data collected from sources in the field. In carrying out its duties and functions, the PIC primarily uses two-way communication so that communication that is built with the external public can work effectively in solving a social problem, especially the DTKS registration problem. obstacles in communicating with external publics through effective primary communication by providing suggestions and solutions to problems experienced by the community related to DTKS registration, so that any problems can be resolved properly and have a good impact on Social Service agencies and the community as the external public.